Launching the AICCRA-Zambia multistakeholder dialogue (MSD) space: Together scaling climate smart agriculture and climate information services in Zambia - Mutenje, Munyaradzi; Pele, Winnie; Ngowenani, Nohayi; Jacobs-Mata, Inga; Minh, Thai Thi; Dahl, Hauke; Mapedza, Everisto D.; Homann-Kee Tui, Sabine; Ngwira, Amos R.; Mudege, Netsayi N.; Kakwasha, Keagan; Mudzungaire, Lizzy; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The MSD launch meeting was co-organized by the International Water Management Institute (IWMI), the international Institute of Tropical Agriculture (IITA), the World Fish and the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). The specific objectives of the CSA-CIS multi-stakeholder dialogue space included: (i) exchanging experiences and expertise on climate-smart agriculture and climate information services (CSA-CIS) innovations across public, private and research sectors​; (ii) sharing insights into the existing multi-stakeholder platforms and processes in the agricultural, livestock, fisheries and water sectors in Zambia​; (iii) identifying interests, common goals, commitments and gaps in the CSA MSP space in Zambia; (iv) co-designing with participants the agenda for the AICCRA-Zambia MSD Space; (v) developing a framework for operationalizing, monitoring, evaluating and learning of the AICCRA Zambia MSD space, and (vi) exploring the most feasible pathways for sustainable and inclusive CSA-CIS scaling in Zambia.